STUDI INDEGENOUS PENYALAHGUNAAN NARKOBA PADA MAHASISWA/I STIKBA JAMBI - Muhammad Hidayat (Universitas Baiturrahim, 2018)
The tendency to increase the use of addictive substances among young people allegedly in line with increasing pressure in all areas of life including students.The study was conducted with the aim to find out how the description of drug abuse in students STIKBA Jambi.Sampling technique used is non-random sampling technique with data collection tool in the form of open-ended questionnaire.It is known that according to the STIKBA students' admission they never use drugs (99%), the reason never to abuse drugs (46%), the effect of never using drugs is to stay healthy (98%), knowledge of where and how acquisition of drugs is not know (85%), source of income is still from parents (99%), the positive effect of never using drugs is body remain healthy (49%), knowledge of drug type is shabu-shabu (24,2%) .According to the STIKBA students' admission they never use drugs (99%) and those who have used drugs (1%) factors causing previous drug abuse is due to social factors, this is based on the conclusions of direct interviews from the informant who stated that the association factor with peers that are too free and uncontrolled cause the students get involved in doing drugs drug misuse.